The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/vop.12114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rebound tonometry in red‐eared slider turtles (Trachemys scripta elegans)

Abstract: Objective To evaluate feasibility and accuracy of intraocular pressure (IOP) measurement by rebound tonometry in adult red-eared slider turtles and determine the effects of manual and chemical restraint on IOP. Animal studied Seventeen adult red-eared slider turtles. Procedures IOP was measured with TonoLab® and TonoVet® tonometers in conscious, unrestrained turtles. To evaluate the effects of manual restraint, turtles were restrained by digital pressure on the rostral head or proximal neck. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
(47 reference statements)
0
28
2
Order By: Relevance
“…Intraocular pressure in wild animals has previously been evaluated using indentation tonometry and applanation tonometry and rebound tonometry . Few studies about IOP in reptiles, especially testudine species, were reported in the literature .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intraocular pressure in wild animals has previously been evaluated using indentation tonometry and applanation tonometry and rebound tonometry . Few studies about IOP in reptiles, especially testudine species, were reported in the literature .…”
Section: Discussionmentioning
confidence: 99%
“…Some available studies with reptile species also report normal ophthalmic parameters and selected clinical tests . Normal values for rebound tonometry and tear production have been reported for red‐eared slider turtles. The objective of this study was to report ocular morphological observations and to perform ophthalmic tests to establish a panel of normal parameters for the red‐eared turtle.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies on various species have validated the use of the Tonovet through correlation with manometry, but no rebound tonometer has been validated in an anuran species. Cannizzo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on various species have validated the use of the Tonovet through correlation with manometry, [18][19][20][21][22] but no rebound tonometer has been validated in an anuran species. Cannizzo et al 11 created calibration curves for both Tonovet and TonoLab in American Bullfrogs, but neither tonometer produced IOP readings that matched the manometer.…”
mentioning
confidence: 99%